Effectiveness of the STEM approach in improving students' mathematical conceptual understanding ability - Mulyani, Sri; Noer, Sri Hastuti (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This quasi-experimental study aims to examine the effectiveness of the STEM approach in enhancing students' understanding of mathematical concepts. The research was motivated by the low learning outcomes and limited student engagement in mathematics learning, which are presumed to result from the use of less effective instructional approaches. The STEM approach was chosen because it enables students to understand mathematical concepts contextually while fostering critical thinking, problem-solving, creativity, and collaboration skills. The sample consisted of 30 students from class VIII-1 and 31 students from class VIII-2, selected through purposive sampling. This study employed a pretest–posttest control group design, with quantitative data obtained from mathematical concept understanding tests. Data were analyzed using nonparametric statistical tests, including the Mann–Whitney U test and proportion test. The results of the Mann–Whitney U test at a 0.05 significance level showed that zcalculated = 2.63 > ztable = 1.96, indicating that Ha was rejected and H0 accepted. The findings revealed a significant difference in the improvement of conceptual understanding between students who received STEM-based instruction and those who experienced conventional learning. Moreover, more than 60% of students taught using the STEM approach achieved a good level of conceptual understanding. Therefore, it can be concluded that the STEM approach is effective in improving students' understanding of mathematical concepts.